Price, convenience, the buying experience, and other motivations for purchasing tobacco and e-cigarettes online - King Jensen, Jessica; Rebentisch, Kayla; Tripp, Hollie; Merten, Julie (Tobacco induced diseases, 2022)
Consumers have shifted to online purchases for many products, including tobacco and e-cigarettes. These shifts have occurred alongside internet tobacco purchasing restrictions being proposed and enacted across the US. The aim of this study was to identify motivations for and against purchasing tobacco and e-cigarettes online, to better understand potential impacts or loopholes. We surveyed 463 US adults who reported ever purchasing tobacco or e-cigarettes in April 2021, using Amazon's Mechanical Turk. Participants who reported purchasing tobacco or e-cigarettes online were asked to describe their reasons for doing so. Those who reported never purchasing online were asked to describe their reasons. Responses were triple-coded and thematically analyzed. Most respondents (n=330; 71.3%) had purchased tobacco or e-cigarettes online. We identified 14 reasons for purchasing tobacco or e-cigarettes online across four themes: price (cheaper online, discounts, bulk purchases, avoiding taxes), product characteristics (availability, quality), buying experience (convenience, time, COVID-19 concerns, avoiding shame, discretion, avoiding salespersons, reading reviews), and curiosity. We identified 13 reasons for not purchasing tobacco or e-cigarette products online across seven themes: buying experience (convenience, time, discretion, seeing the product), concerns (legality, safety, quality), consumption, price, supporting local, unaware, and uninterested. Both online and offline purchasers stated price and convenience motivated their choice to purchase tobacco or e-cigarettes online. Though few participants mentioned purchasing illicit products, concerns about legality and quality of online purchases were raised, and there was some awareness that online purchases attracted lower taxation.